(untitled) (Altre Modernità, 2022)
The outbreak of COVID-19 has produced serious consequences in social and economic terms. The speed at which this pandemic spread in the initial weeks led governments to take drastic measures in order to contain its devastating effects. To this end, lockdowns were imposed in many countries which lasted for months, affecting people’s lives in important respects. The way in which the general public was apprised of these restrictions deserves attention, as communication plays a major role at the time of implementing measures impacting on people’s freedoms. Based on these considerations, this paper provides a comparison of the rhetorical devices adopted by national governments to inform the public of the beginning of the lockdown. Specifically, the statements with which the Prime Ministers of Italy and the UK announced the implementation of lockdown measures will be examined, with a view to investigating their linguistic features in both Italian and English.